The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acs.energyfuels.5b00339
|View full text |Cite
|
Sign up to set email alerts
|

Co-processing of Dry Bio-oil, Catalytic Pyrolysis Oil, and Hydrotreated Bio-oil in a Micro Activity Test Unit

Abstract: Fast pyrolysis technology is currently moving forward to commercialization, and demonstration plants are at the commissioning stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 22 publications
(55 reference statements)
2
53
1
Order By: Relevance
“…During their research, they found out that the co-processing of 20 % of the biooil subjected to HDO with 80% of VGO led to the level of gasoline output comparable to the processing of traditional raw materials -the cracking of pure VGO. Similar results were obtained in the work by Lindfors [40], in which hydrogenated pyrolysis oil yielded 74% by weight of liquid products compared to 69 % (dry pyrolysis oil) for untreated liquid ( Table 5). The resulting gasoline is characterized by good performance characteristics similar to the traditional processing of pure vacuum gas oil and their use does not require any changes in the fuel consumption infrastructure.…”
Section: Co-processing Of Bio-oil With Petroleum Products In the Condsupporting
confidence: 89%
“…During their research, they found out that the co-processing of 20 % of the biooil subjected to HDO with 80% of VGO led to the level of gasoline output comparable to the processing of traditional raw materials -the cracking of pure VGO. Similar results were obtained in the work by Lindfors [40], in which hydrogenated pyrolysis oil yielded 74% by weight of liquid products compared to 69 % (dry pyrolysis oil) for untreated liquid ( Table 5). The resulting gasoline is characterized by good performance characteristics similar to the traditional processing of pure vacuum gas oil and their use does not require any changes in the fuel consumption infrastructure.…”
Section: Co-processing Of Bio-oil With Petroleum Products In the Condsupporting
confidence: 89%
“…Co-processing 20 wt. % bio-component also produced more coke than catalytic cracking of pure VGO overall (Lindfors, Paasikallio, Kuoppala, Reinikainen, Oasmaa & Solantausta, 2015). Thegarid and colleagues (2014) are of the view that crude bio-oil cannot be co-processed without upgrading the bio-oil first, either by HDO or catalytic pyrolysis.…”
Section: Bio-oil Co-processing In a Crude-oil Refinerymentioning
confidence: 99%
“…a. (Lindfors et al, 2015) b. (Jechura, 2016) The higher MSP of upgraded bio-oil can be justified over the lower MSP of crude bio-oil by its superior quality and suitability for co-processing.…”
Section: Profitability Analysismentioning
confidence: 99%
“…In the United States, FCC and the alkylation unit it supplies produce about 50% of the gasoline pool in most refineries [17]. Co-processing of bio-oils with conventional petroleum-based products such as VGO is an attractive initial option to make use of renewable biomass as a fuel source, while leveraging existing refinery infrastructure [14][15][18][19][20][21][22][23][24]. However, the use of untreated bio-oils as a co-processing feedstock results in processing difficulties in the FCC due to plugging from increased coke deposition [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%